National Society of Genetic Counselors Code of Ethics. Issue 1 (27th October 2017) - ,
Abstract: This document is the revised Code of Ethics of the National Society of Genetic Counselors (NSGC) that was adopted in April 2017 after majority vote of the full membership of the NSGC. The explication of the revisions is published in this volume of the Journal of Genetic Counseling. This is the fourth revision to the Code of Ethics since its original adoption in 1992.